2020
DOI: 10.1039/d0ra00217h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, photo and acidochromic properties of spiropyran-containing methanofullerenes

Abstract: Spiropyran-containing methanofullerenes able to rapidly and reversibly respond to optical and chemical stimuli were synthesized for the first time by the Bingel–Hirsch reaction and catalytic cycloaddition of diazo compounds to carbon clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…This is indicated by the considerable difference between the photodegradation efficiency of compounds 2′ and 1′ ( Table 1 , Figure 3 ). It was found that hybrid compound 2′ is much more stable to irreversible phototransformations (τ 1/2 > 700 s) than compound 1′ (τ 1/2 = 64 s), which is consistent with published data [ 3 , 25 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This is indicated by the considerable difference between the photodegradation efficiency of compounds 2′ and 1′ ( Table 1 , Figure 3 ). It was found that hybrid compound 2′ is much more stable to irreversible phototransformations (τ 1/2 > 700 s) than compound 1′ (τ 1/2 = 64 s), which is consistent with published data [ 3 , 25 ].…”
Section: Resultssupporting
confidence: 91%
“…Among the broad spectrum of organic photochromic systems, spiropyrans are the most interesting representatives, since their spectral, photochemical, and luminescence characteristics can be varied over fairly broad ranges. The possibility of interconversion between two isomers of spiropyrans under the action of external stimuli [ 1 , 2 , 3 ] is of considerable interest for the various applications in science and technology. Owing to their unique properties, spiropyrans are used for the manufacture of photochromic glasses [ 4 ] and as chemosensors [ 5 ], regulators of chemical reactions [ 6 ], optoelectronic and holographic devices [ 7 ], memory cells [ 8 ], regulators of membrane permeability [ 9 ], and molecular engines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Спиропиран 3 был получен по хорошо описанной методике [4]. Синтез и свойства соединения 4 описаны ранее [5].…”
Section: экспериментальная частьunclassified
“…1–8 Spiropyran, as one of the most classical stimuli-responsive materials, undergoes reversible structural isomerization upon a variety of stimuli, such as light, pH, temperature, metal ions, and solvent polarity. 9–12 Spiropyran-based materials have been extensively investigated and widely applied in many fields, such as bioimaging, controlled release, data storage, and sensors. 13–16…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Spiropyran, as one of the most classical stimuli-responsive materials, undergoes reversible structural isomerization upon a variety of stimuli, such as light, pH, temperature, metal ions, and solvent polarity. [9][10][11][12] Spiropyran-based materials have been extensively investigated and widely applied in many elds, such as bioimaging, controlled release, data storage, and sensors. [13][14][15][16] There has been great interest in developing stimulusresponsive nanoparticles ascribing to their advantages such as, good water dispersibility, excellent biocompatibility and the ability for further functionalization.…”
Section: Introductionmentioning
confidence: 99%